Alzheimer's disease: assessing the therapeutic potential of anti-Aβ (Beta-Amyloid) treatments: Alzheimer's disease and anti-Aβ treatments - Almutairi, Jawza A. (Cellular and Molecular Biology, 2025)
One of the most common forms of dementia and a neurodegenerative illness is Alzheimer's disease (AD), which is distinguished by impaired memory and cognitive dysfunction. Decades of research have been devoted to determining its etiology, pathogenic processes, and biomarkers to facilitate early identification and clinical investigations for therapy. Neural atrophy and broken connections between neurons are the outcomes of the illness. The amyloid beta (Aβ) cascade is among the most widely recognized and important hypotheses of the numerous hypotheses regarding the pathogenesis of AD. This theory suggests that the breakdown of the amyloid precursor protein (APP) produces Aβ monomers. These monomers are then converted into hazardous oligomers, which in turn form β-sheets, fibrils, and plaques after being formed. The amyloid cascade theory was covered in this review, along with a summary of how it is used to diagnose and treat Alzheimer's. Specifically, we covered the drawbacks, potential, and significant unsolved issues with the anti-Aβ therapy that is now in use, as well as plans for more research and the creation of more workable Aβ-targeted methods to optimize AD early detection and management.